Phylogeny of Drosophila saltans group (Diptera: Drosophilidae) based on morphological and molecular evidence - Roman, Bruna Emilia [UNESP]; Santana, Diego J.; Prediger, Carolina [UNESP]; Madi-Ravazzi, Lilian [UNESP] (Public Library of Science (PLoS), 2022)
Drosophila saltans group belongs to the subgenus Sophophora (family Drosophilidae), and it is subdivided into five subgroups, with 23 species. The species in this group are widely distributed in the Americas, primarily in the Neotropics. In the literature, the phylogenetic reconstruction of this group has been performed with various markers, but many inconsistencies remain. Here, we present a phylogenetic reconstruction of the saltans group with a greater number of species, 16 species, which is the most complete to date for the saltans group and includes all subgroups, in a combined analysis with morphological and molecular markers. We incorporated 48 morphological characters of male terminalia, the highest number used to date, and molecular markers based on mitochondrial genes COI and COII. Based on the results, which have recovered the five subgroups as distinct lineages, we propose a new hypothesis regarding the phylogenetic relationships among the subgroups of the saltans group. The relationships of the species within the sturtevanti and elliptica subgroups were well supported. The saltans subgroup showed several polytomies, but the relationship between the sibling species D. austrosaltans and D. saltans and their close relation with D. nigrosaltans were well supported in the molecular and total evidence analyses. The morphological analysis additionally supported the formation of the clade D. nigrosaltans—D. pseudosaltans. The observed polytomies may represent synchronous radiations or have resulted from speciation rates that have been too fast relative to the pace of substitution accumulation.